Enhancement of Hippocampal Plasticity by Physical Exercise as a Polypill for Stress and Depression: A Review - Li, Ang; Yau, Suk-yu; Machado, Sergio; Wang, Pingjie; Yuan, Ti-Fei; So, Kwok-Fai (CNS & Neurological Disorders - Drug Targets, 2019)
Generation of newborn neurons that form functional synaptic connections in the dentate gyrus of adult mammals, known as adult hippocampal neurogenesis, has been suggested to play critical roles in regulating mood, as well as certain forms of hippocampus-dependent learning and memory. Environmental stress suppresses structural plasticity including adult neurogenesis and dendritic remodeling in the hippocampus, whereas physical exercise exerts opposite effects. Here, we review recent discoveries on the potential mechanisms concerning how physical exercise mitigates the stressrelated depressive disorders, with a focus on the perspective of modulation on hippocampal neurogenesis, dendritic remodeling and synaptic plasticity. Unmasking such mechanisms may help devise new drugs in the future for treating neuropsychiatric disorders involving impaired neural plasticity.
Keywords: hippocampal neurogenesis